Inventarytation of Medicinal Plants in Leang-Leang Village, Bantimurung District, Maros Regency - Iriani, Rahma; Amin, Asni; Nur Azizah, Rizqi (Journal of Pharmaceuticals and Natural Sciences, 2024)
This study aimed to obtain data, information, and an inventory of medicinal plant species used by the community in Leang-Leang Village. The type of research used was descriptive qualitative research using purposive sampling. Data collection techniques were completed through questionnaires and interviews with 96 Leang- Leang Village respondents. The results reported 43 types of medicinal plants comprising 31 families utilized by the people of Leang-Leang Village to maintain health and treat 24 types of certain diseases. The people of Leang-Leang Village utilized the medicinal plants through the leaves, stems, rhizomes, tubers, roots, sap, fruit, and flowers, with the highest percentage of 78% on the leaves, for instance: guava leaves, soursop leaves, miana leaves, and other types of leaves. The most commonly used method of processing medicinal plants was by boiling, with a percentage of 69%. Besides, it was drunk as the most common way of consumption, with a rate of 77%.